Ologen in surgical management of glaucomatous optic neuropathy - Duchnik, Irmina; Starzycka-Bigaj, Ewa; Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2017)
The inability to inhibit the progression of optic nerve damage and visual field defects despite conservative therapy constitutes an indication for surgical intervention in glaucoma. Trabeculectomy is still the “golden standard” in glaucoma filtering surgery. The main causes of surgical failure are episcleral fibrosis and subconjunctival scarring, which especially affect younger people and patients after multiple operations on the same eye. In order to prolong the patency of the fistula and to achieve a lower intraocular pressure, anti-metabolic agents such as antimetabolites and collagen matrix ologen are used during glaucoma surgery. The aim of this study is to review the current literature on efficacy and safety of ologen use in glaucoma surgery.